Discover answers to your questions with Westonci.ca, the leading Q&A platform that connects you with knowledgeable experts. Join our platform to connect with experts ready to provide detailed answers to your questions in various areas. Explore comprehensive solutions to your questions from knowledgeable professionals across various fields on our platform.

\begin{tabular}{|l|l|}
\hline \multicolumn{1}{|c|}{Statement} & Reason \\
\hline [tex]$3(5x + 1) = 13x + 5$[/tex] & Given \\
\hline [tex]$15x + 3 = 13x + 5$[/tex] & Distributive Property \\
\hline [tex]$15x - 13x + 3 = 13x + 5 - 13x$[/tex] & Subtraction Property of Equality \\
\hline [tex]$2x + 3 = 5$[/tex] & Simplify \\
\hline [tex]$2x + 3 - 3 = 5 - 3$[/tex] & Subtraction Property of Equality \\
\hline [tex]$2x = 2$[/tex] & Simplify \\
\hline [tex]$\frac{2x}{2} = \frac{2}{2}$[/tex] & Division Property of Equality \\
\hline [tex]$x = 1$[/tex] & Simplify \\
\hline
\end{tabular}


Sagot :

Great! Let's go through the step-by-step solution for the given equation [tex]\(3(5x + 1) = 13x + 5\)[/tex], filling in the reasons for each step in the provided table format.

\begin{tabular}{|l|l|}
\hline \multicolumn{1}{|c|}{Statement} & \multicolumn{1}{|c|}{Reason} \\
\hline [tex]$3(5x + 1) = 13x + 5$[/tex] & Given equation \\
\hline [tex]$15x + 3 = 13x + 5$[/tex] & Distribute the 3 to terms inside the parentheses \\
\hline [tex]$15x - 13x + 3 = 13x + 5 - 13x$[/tex] & Subtract [tex]$13x$[/tex] from both sides \\
\hline [tex]$2x + 3 = 5$[/tex] & Combine like terms \\
\hline [tex]$2x + 3 - 3 = 5 - 3$[/tex] & Subtract 3 from both sides \\
\hline [tex]$2x = 2$[/tex] & Simplify both sides \\
\hline [tex]$\frac{2x}{2} = \frac{2}{2}$[/tex] & Division property of equality: divide both sides by 2 \\
\hline [tex]$x = 1$[/tex] & Solution simplified \\
\hline
\end{tabular}

To clarify the process:

1. Distribute: Multiply the 3 by both terms inside the parentheses: [tex]\(3(5x + 1) \rightarrow 15x + 3\)[/tex].
2. Combine Like Terms: Move the variable terms to one side and the constants to the other side.
3. Subtract: Isolate the variable by getting rid of the constant term on the same side as the variable.
4. Divide: Solve for the variable by dividing both sides by the coefficient of the variable term.

Thus, the solution to the equation [tex]\(3(5x + 1) = 13x + 5\)[/tex] is [tex]\(x = 1\)[/tex].